Recent Nitrogen Storage and Accumulation Rates in Mangrove Soils Exceed Historic Rates in the Urbanized San Juan Bay Estuary (Puerto Rico, United States) - Wigand, Cathleen; Oczkowski, Autumn J.; Branoff, Benjamin L.; Eagle, Meagan; Hanson, Alana; Martin, Rose M.; Balogh, Stephen; Miller, Kenneth M.; Huertas, Evelyn; Loffredo, Joseph; Watson, Elizabeth B. (Frontiers in Forests and Global Change, 2021)
Tropical mangrove forests have been described as “coastal kidneys”, promoting sediment deposition and filtering contaminants, including excess nutrients. Coastal areas throughout the world are experiencing increased human activities, resulting in altered geomorphology, hydrology, and nutrient inputs. To effectively manage and sustain coastal mangroves, it is important to understand nitrogen (N) storage and accumulation in systems where human activities are causing rapid changes in N inputs and cycling. We examined N storage and accumulation rates in recent (1970 – 2016) and historic (1930 – 1970) decades in the context of urbanization in the San Juan Bay Estuary (SJBE, Puerto Rico), using mangrove soil cores that were radiometrically dated. Local anthropogenic stressors can alter N storage rates in peri-urban mangrove systems either directly by increasing N soil fertility or indirectly by altering hydrology. Nitrogen accumulation rates were greater in recent decades than historic decades at Piñones Forest and Martin Peña East. Martin Peña East was characterized by high urbanization, and Piñones, by the least urbanization in the SJBE. The mangrove forest at Martin Peña East fringed a poorly-drained canal and often received raw sewage inputs, with N accumulation rates ranging from 17.7 – 37.9 g m-2 y-1 in recent decades. The Piñones Forest was isolated and had low flushing, possibly exacerbated by river damming, with N accumulation rates ranging from 18.6 – 24.2 g m-2 y-1 in recent decades. Nearly all (96.3%) of the estuary-wide mangrove N (9.4 Mg ha-1) was stored in the soils with 7.1 Mg ha-1 sequestered during 1970-2017 (0-18 cm) and 2.3 Mg ha-1 during 1930-1970 (19-28 cm). Estuary-wide mangrove soil N accumulation rates were over twice as great in recent decades (0.18 ± 0.002 Mg ha-1y-1) than historically (0.08 ± 0.002 Mg ha-1y-1). Nitrogen accumulation rates in SJBE mangrove soils in recent times were 2-fold larger than the rate of human-consumed food N that is exported as wastewater (0.08 Mg ha-1 y-1), suggesting the potential for mangroves to sequester human-derived N. Conservation and effective management of mangrove forests and their surrounding watersheds in the Anthropocene are important for maintaining water quality in coastal communities throughout tropical regions.